Effects of Flaxseed and pH on the Emulsion Properties of Beef by Using a Model System - Şükrü Kurt; Huriye Gözde Ceylan (Turkish Journal of Agriculture: Food Science and Technology)
The effects of ground flaxseed (0-0.5%) and pH (3.88-8.12) on the emulsion properties of beef were studied using a model system. A central composite rotatable design was used to determine the response surface. pH, flaxseed and their interactions had significant effects on the emulsion properties of beef. pH and the interaction between pH and flaxseed increased emulsion capacity (EC). Flaxseed and pH increased emulsion stability (ES) until a critical point, which was reached at a flaxseed level of 0.42% and a pH of 7.02. pH decreased emulsion density (ED) and increased emulsion activity (EA). Moreover, the interaction between pH and flaxseed on EA was found to be significant. pH and flaxseed increased emulsion viscosity (EV), and the increasing rate was higher in basic medium than acidic.